-3(3x-11)+2(5x+7)=

Simple and best practice solution for -3(3x-11)+2(5x+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3x-11)+2(5x+7)= equation:


Simplifying
-3(3x + -11) + 2(5x + 7) = 0

Reorder the terms:
-3(-11 + 3x) + 2(5x + 7) = 0
(-11 * -3 + 3x * -3) + 2(5x + 7) = 0
(33 + -9x) + 2(5x + 7) = 0

Reorder the terms:
33 + -9x + 2(7 + 5x) = 0
33 + -9x + (7 * 2 + 5x * 2) = 0
33 + -9x + (14 + 10x) = 0

Reorder the terms:
33 + 14 + -9x + 10x = 0

Combine like terms: 33 + 14 = 47
47 + -9x + 10x = 0

Combine like terms: -9x + 10x = 1x
47 + 1x = 0

Solving
47 + 1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-47' to each side of the equation.
47 + -47 + 1x = 0 + -47

Combine like terms: 47 + -47 = 0
0 + 1x = 0 + -47
1x = 0 + -47

Combine like terms: 0 + -47 = -47
1x = -47

Divide each side by '1'.
x = -47

Simplifying
x = -47

See similar equations:

| 6+(2+1)=5-5t | | 8y+1=2y+25 | | 4x-15=3x+9 | | 0.8n+9=0.2(4n+45) | | 2x+5+6x=3x+15 | | 7y-1=35-5y | | 0.4(2x+6)+0.1=0.5(2Z-3) | | 2(x+y)+6n(x+y)= | | 49x^2+4=28 | | 0=-1.66x+79.21 | | 0=-1.66+79.21 | | 10a-11=5a+4 | | .5w+90=4w+90 | | 18x-6=22x-78 | | f(3)=3n | | 10r=9r+18 | | 4-k=-4 | | 0.5(2.5x+4)=6x+4 | | f(2)=3n | | -7x+5x-9x=-22 | | 6w-14=3w+4 | | 180(30-2)=s | | 16x^2+3x-124=0 | | 3-4x=10(x+1) | | 11=1y+2 | | 6(x+8)=63 | | b^2+16b+26=-3 | | x^2+y^2+2x+14y+50=0 | | 0.50x+0.05(10-x)=0.10(-31) | | y=(6-x)(7-6x) | | 2(m-7)=42 | | 11-7+x=3-2x-11 |

Equations solver categories